Protective effects of bifidobacteria against enteropathogens. Issue 6 (8th July 2019) - Aw, Wanping; Fukuda, Shinji
Summary: Recent major advances in metagenomics and metabolomics technologies have enabled us to collect more data on the gut microbiome and metabolome to evaluate its influence on host health. In this short opinion article, we have chosen to focus on summarizing the protective mechanisms of bifidobacteria, a highly regarded probiotic, and it's metabolite: acetate; against enteropathogens, specifically in the E. coli O157:H7 mice model. We advocate for using a novel approach metabologenomics, which is an integration of metagenomic and metabolomic information on a systems biology‐wide approach to better understand this interplay between gut microbiome and host metabolism. Abstract : In this short opinion article, we have chosen to focus on summarizing the protective mechanisms of bifidobacteria, a highly regarded probiotic, and it's metabolite: acetate; against enteropathogens, specifically in the E. coli O157:H7 mice model. We advocate for using a novel approach‐ metabologenomics, which is an integration of metagenomic and metabolomic information on a systems biology‐wide approach to better understand this interplay between gut microbiome and host metabolism.